2011
DOI: 10.1001/archfacial.2011.28
|View full text |Cite
|
Sign up to set email alerts
|

1550-nm Nonablative Laser Resurfacing for Facial Surgical Scars

Abstract: Preliminary data suggest improved aesthetic results, demonstrating the potential use of fractional photothermolysis as a scar revision technique. Future studies with a longer follow-up period could elucidate the role of fractional photothermolysis in more permanent scar improvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 16 publications
1
15
0
1
Order By: Relevance
“…The patient declined the other methods because of risk of infection, further scaring, hypopigmentation, hyperpigmentation, and anxiety of nose necrosis. Non-ablative fractional laser was chosen because of its safety benefit and easily controlled method compared to other methods [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…The patient declined the other methods because of risk of infection, further scaring, hypopigmentation, hyperpigmentation, and anxiety of nose necrosis. Non-ablative fractional laser was chosen because of its safety benefit and easily controlled method compared to other methods [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Fraxel ® (Fraxel SR1500 RE:Store; Solta Medical, Hayward, CA, USA) is a 1550 nm erbium‐doped fiber laser that creates non‐ablative dermal microthermal injury zones. Facial surgical scars between six months and five years were treated every four weeks for four treatments at 40 mJ/cm 2 energy and treatment level 4, covering 11% of the treated area . Observers rated significant improvement in scar pigmentation, thickness, relief, and pliability but not vascularization.…”
Section: Scar Prevention and Remodelingmentioning
confidence: 98%
“…35 Pham et al also found that postsurgical scars treated with four sessions of NAFR utilizing a 1,550-nm laser resulted in subjective improvement in 13 patients' ratings of color, stiffness, thickness, and irregularity as well. 36 Burn scars, which also have been difficult to treat historically, were shown in one randomized controlled study to respond with improved skin texture after treatment with a nonablative fractional laser. Three monthly treatments were performed with a 1,540-nm instrument and blinded evaluations were performed 1 and 3 months after the final procedure.…”
Section: Clinical Data For Acne and Surgical Scarringmentioning
confidence: 99%